Red Blood Cell Passage of Small Capillaries Is Associated with Transient Ca2+-mediated Adaptations - Danielczok, Jens G.; Terriac, Emmanuel; Hertz, Laura; Petkova-Kirova, Polina; Lautenschläger, Franziska; Laschke, Matthias W.; Kaestner, Lars (Frontiers in Physiology, 2017)
When red blood cells (RBCs) pass constrictions or small capillaries they need to pass apertures falling well below their own cross section size. We used different means of mechanical stimulations (hypoosmotic swelling, local mechanical stimulation, passing through microfluidic constrictions) to observe cellular responses of human RBCs in terms of intracellular Ca2+-signalling by confocal microscopy of Fluo-4 loaded RBCs. We were able to confirm our in vitro results in a mouse dorsal skinfold chamber model showing a transiently increased intracellular Ca2+ when RBC were passing through small capillaries in vivo. Furthermore we performed the above-mentioned in vitro experiments as well as measurements of RBCs filterability under various pharmacological manipulations (GsMTx-4, TRAM-34) to explore the molecular mechanism of the Ca2+-signalling. Based on these experiments we conclude that mechanical stimulation of RBCs activates mechano-sensitive channels most likely Piezo1. This channel activity allows Ca2+ to enter the cell, leading to a transient activation of the Gardos channel associated with K+, Cl- and water loss, i.e. with a transient volume adaptation facilitating the passage of the RBCs through the constriction.